Analysis of the Factor that’s Influence an Increase of Cost of Post-Operative Care on the Central Surgical Installation at Jombang General Hospitals - Siswoyo, Cipto; Suprapto, Sentot Imam; Siyoto, Sandu (Master of Public Health Program Universitas STRADA Indonesia, 2020)
Post-operative treatment and recovery anestesia desperately need professional nursing skills. Skills in the post-operative care of patients is urgently needed to prevent complications that lengthening the home care pain or harm themselves. The old days of post-operative patient care need great attention because of some complications can occur after surgery if not handled properly, can make long day care be long that can eventually lead to the occurrence of the increase in the cost of treatment to the patients as well as the hospital. The purpose of the research is to analyze the cost of post-operative care enhancement due to hypothermia on the Central Surgical Installation At Jombang General Hospitals. The research design was analytic observational with a quantitative approach. Research variables i.e. factor causes the occurrence of hypothermia as the independent variable, the dependent variable costs increase. This research population throughout the patient's post-operative at Central Surgical Installation At Jombang General Hospitals with the average number of patients per month as much as 326 patients. Samples taken with the technique of simple random sampling as much as 180 respondents. Data is collected with instruments ceklist and processed in coding, editing, tabulating and scoring as well as tested with dummy regression test. The regression results show that the dummy variables that influence directly are in long treatment in recovery room and hipotermi events because the value of a p value < 0.05. While variable, the type of anaesthetic, BMI and long operations have no effect directly against the increase in the cost of treatment in the recovery room space. The existence of a decrease in body temperature of the patient requires more intensive than the handling of patients in a State of normal body temperature, and also requires additional equipment hipotermi patients, oxygen and heating to be able to restore the patient's body temperature in normal conditions, thus affecting an increase in treatment costs in the recovered unconscious